Promoting axon regeneration in the adult CNS by modulation of the melanopsin/GPCR signaling - Li, Songshan; Yang, Chao; Zhang, Li; Gao, Xin; Wang, Xuejie; Liu, Wen; Wang, Yuqi; Jiang, Songshan; Wong, Yung Hou; Zhan, Yifeng; 张翼凤; Liu, Kai (Proceedings of the National Academy of Sciences - PNAS, 2016)
Cell-type–specific G protein-coupled receptor (GPCR) signaling regulates distinct neuronal responses to various stimuli and is essential for axon guidance and targeting during development. However, its function in axonal regeneration in the mature CNS remains elusive. We found that subtypes of intrinsically photosensitive retinal ganglion cells (ipRGCs) in mice maintained high mammalian target of rapamycin (mTOR) levels after axotomy and that the light-sensitive GPCR melanopsin mediated this sustained expression. Melanopsin overexpression in the RGCs stimulated axonal regeneration after optic nerve crush by up-regulating mTOR complex 1 (mTORC1). The extent of the regeneration was comparable to that observed after phosphatase and tensin homolog (Pten) knockdown. Both the axon regeneration and mTOR activity that were enhanced by melanopsin required light stimulation and Gq/11 signaling. Specifically, activating Gq in RGCs elevated mTOR activation and promoted axonal regeneration. Melanopsin overexpression in RGCs enhanced the amplitude and duration of their light response, and silencing them with Kir 2.1 significantly suppressed the increased mTOR signaling and axon regeneration that were induced by melanopsin. Thus, our results provide a strategy to promote axon regeneration after CNS injury by modulating neuronal activity through GPCR signaling.